Re: solve and simplify. force left hand side to be 0==

*To*: mathgroup at smc.vnet.net*Subject*: [mg51179] Re: [mg51152] solve and simplify. force left hand side to be 0==*From*: Andrzej Kozlowski <akoz at mimuw.edu.pl>*Date*: Thu, 7 Oct 2004 05:26:07 -0400 (EDT)*References*: <200410060834.EAA24236@smc.vnet.net>*Sender*: owner-wri-mathgroup at wolfram.com

On 6 Oct 2004, at 17:34, sean kim wrote: > *This message was transferred with a trial version of CommuniGate(tm) > Pro* > > consider a system such as, > > sde = { > 0==v1-d1 e[0]+k2 es[0]-k1 e[0] s[0], > 0==-k2 es[0]-k3 es[0]+k1 e[0] s[0], > 0==k3 es[0]-d3 p[0], > 0==v2+k2 es[0]-d2 s[0]-k1 e[0] s[0]}; > > sv = {e[0],es[0],p[0],s[0]}; > > Solve[sde[[1]], e[0]] > > sde1= sde/.% > > %//Simplify > > shows once I simplify the solution, the structure of > 0== stuff... is lost. > > is there anyway to force Simplify to keep the > structure so that left hand side is always 0== stuff? > > thanks in advance for any insights. > > > sean > You can just Map Simplify onto the third level of your expression: Map[Simplify, sde1, {3}] {{True, 0 == (-k2)*es[0] - k3*es[0] + (k1*(v1 + k2*es[0])*s[0])/(d1 + k1*s[0]), 0 == k3*es[0] - d3*p[0], 0 == v2 + k2*es[0] - d2*s[0] - (k1*(v1 + k2*es[0])*s[0])/(d1 + k1*s[0])}} The first equation turned into 0===0 and hence you got True. But the rest is as you wanted. Andrzej Kozlowski Chiba, Japan http://www.akikoz.net/~andrzej/ http://www.mimuw.edu.pl/~akoz/

**References**:**solve and simplify. force left hand side to be 0==***From:*sean kim <sean_incali@yahoo.com>